(untitled) (Carte Romanze, 2020)
The Cantiga de Santa Maria n. 369 tells how a ring was miraculously found inside a fish after it had been stolen by deception from a woman devoted to the Virgin who lived in the Portuguese town of Santarém. An internal reference to the Gospel episode of St. Peter, who finds a coin in the mouth of a fish, has conditioned the only hypothesis relating to the source of inspiration of this Cantiga, although the latter actually presents a more complex narrative dynamic than the miracle related in Mt. 17, 24-27. If we look at the non-Marian hagiographic literature prior to Alfonso X’s period of activity, we can instead hypothesize how the Cantiga was inspired by a group of récits which, in addition to presenting the same motif as ‘the fish and the ring’, they also reveal a similar plot. Among these, the miracle of the sentem argenteam performed by Saint Brigid of Ireland stands out. In addition, this miracle was taken up, starting from the XIIIth century, by Vincent of Beauvais in his Speculum Historiale and by an anonymous author in the Orto do Esposo, both related to the Peninsular cultural environment. Other secondary details of the story would show debts with a work almost coeval with the Cantigas, namely the Dialogus Miraculorum written by Cesarius of Heisterbach